Analisis Manajemen Risiko Teknologi Informasi dengan ISO 31000:2018 pada PT Bayu Buana Tbk - Devy Putri Natalie; Augie David Manuputty (JURIKOM (Jurnal Riset Komputer), 2022)
At this time, almost all organizations/companies use IT to support their business processes. The presence of IT makes work easier for organizations/companies. Especially with the Covid-19 pandemic which has had a huge impact on several business sectors. One of them is in the travel services business sector. In a situation swayed by the pandemic, PT Bayu Buana Tbk, which is one of the companies engaged in the travel services business, chose to change its business strategy by using IT to survive amidst the pandemic. This decision is very appropriate and in line with the mission and vision of the company. However, the advantages provided by IT, have disadvantages in the form of risks that can occur. This risk is unavoidable. However, the impact can be minimized with IT risk management. Therefore, researchers are interested in conducting IT risk management at PT Bayu Buana Tbk. To assist researchers in conducting (qualitative) analysis, researchers use the ISO 31000:2018 framework. From the results of the study, there are 21 possible risks which are divided into 3 risk levels, namely 8 high-level risks, 10 medium-level risks, and 3 low-level risks. It was also found answers to whether or not the strategy implemented by the company and the good/bad implementation of IT at branch offices were other objectives of the research. So that researchers can provide suggestions to help the company achieve its vision and mission